Management of status epilepticus in patients with liver or kidney disease: a narrative review. (2nd November 2021) - Mastroianni, Giovanni; Iannone, Luigi Francesco; Roberti, Roberta; Gasparini, Sara; Ascoli, Michele; Cianci, Vittoria; De Sarro, Giovambattista; Gambardella, Antonio; Labate, Angelo; Brigo, Francesco; Russo, Emilio; Aguglia, Umberto; et al.
ABSTRACT: Introduction : Status epilepticus (SE) is a neurologic and medical emergency with significant related morbidity and mortality. Hepatic or renal dysfunction can considerably affect the pharmacokinetics of drugs used for SE through a variety of direct or indirect mechanisms. Areas Covered : This review aims to focus on the therapeutic management of SE in patients with hepatic or renal impairment, highlighting drugs' selection and dose changes that may be necessary due to altered drug metabolism and excretion. The references for this review were identified by searches of PubMed and Google Scholar until May 2020. Expert opinion : According to literature evidence and clinical experience, in patients with renal disease, the authors suggest considering lorazepam as the drug of choice in pre-hospital and intra-hospital early-stage SE, phenytoin in definite SE, propofol in refractory or super-refractory SE. In patients with liver disease, the authors suggest the use of lorazepam as drug of choice in pre-hospital and intra-hospital early-stage SE, lacosamide in definite SE, propofol in refractory or super-refractory SE. A list of preferred drugs for all SE stages is provided.